High prevalence of risk behaviour concurrent with links to other high-risk populations: a potentially explosive HIV epidemic among men who have sex with men in Guangzhou, China. Issue 5 (8th April 2009) - He, Q; Wang, Y; Lin, P; Raymond, H F; Li, Y; Yang, F; Zhao, J; Li, J; Ling, L; McFarland, W
Abstract : Objectives: HIV disproportionately affects men who have sex with men (MSM), but HIV prevalence among MSM in Guangzhou has not shown the rapid increasing trend as it has elsewhere in China. The aim of this study is to detect the epidemic and to determine the characteristics of MSM in Guangzhou susceptible to HIV. Methods: A cross-sectional survey with serological testing for HIV, syphilis, HBV and HCV through long-chain referral sampling strategy to help control the bias generated from non-statistic sampling. Results: The most important features of MSM in Guangzhou are being young and mobile, and of comparable education and income level to that of the general population. The HIV prevalence was 1.3% (95% CI 0.3 to 2.7%) in 2006. Many HIV risk factors were identified: low awareness of HIV risk perception and prevention, high prevalence of diverse, multiple partners and versatile sexual role, more than half of them actively having sex with women, low persistent condom use with both male and female partners, commercial sex and one out of 27 practising needle or syringe sharing during illicit drug use. Conclusion: HIV has been introduced into MSM in Guangzhou. Demographic and behavioural risk factors and overlapping risk populations contribute to a potentially rapidly rising epidemic among MSM and the potential for a bridge to female partners in Guangzhou if timely and effective interventions are not implemented.